A CNC tooth grinding method for formate face hobbed hypoid gears. (February 2020) - Zhang, Weiqing; Guo, Xiaodong; Wang, Yawen; Wen, Yikai; Lin, Chia-Ching; Lim, Teik C.
Highlights: A hypoid tooth grinding method is proposed using large conical grinding wheel. The proposed method can be used for mass production without theoretical deviation. Interference is checked in grinding wheel coordinate to reduce computational cost. Tilting the grinding wheel axis is used to avoid the interference effectively. Abstract: Face hobbing is an efficient process for hypoid gear cutting. However, the continuous indexing process renders it inapplicable for tooth grinding, which limits the further improvement of gear accuracy and transmission performance. In this paper, a tooth grinding method using large diameter conical grinding wheel for Formate® face hobbed hypoid gears (FFHHG) was proposed. The generator of conical grinding wheel was used to replace the cutter blade of the face hobbing process. By controlling the conical grinding wheel, the generator of the grinding wheel can be tangentially in contact with the tooth profile curve of the FFHHG. The sweeping of the generator of the grinding wheel along the extended epicycloidal tooth curve can grind one tooth surface accurately without theoretical deviation. Firstly, the tooth surface was formulated and the geometric parameters of the working side of the grinding wheel were determined to avoid the curvature interference between the grinding wheel and the ground tooth surface. Then, a five-axis tooth grinding tool location model was established to position the grinding wheel and the tooth surface correctly. The interference of the non-working side of grinding wheel was checked and if necessary the grinding wheel axis can be tilted to avoid interference. Finally, the above processes were verified by case analysis and grinding simulations. This study can be employed to improve the pitch accuracy of FFHHG and reduce the tooth profile deviation.